GENDER DIFFERENCES IN VISUOSPATIAL WORKING MEMORY - Safal Srivastava; Pal, Reetika (International Journal of Psychosocial Rehabilitation, 2020)
Visual-spatial working memory measures are widely used in clinical and experimental settings. Sex differences in visual-spatial working memory have important implication for research, theory, and practice, but they have yet to be quantified. The objective of this research is to study the gender differences on the visuo-spatial working memory. Since there aren’t enough researches regarding the relationship of gender and visuo-spatial short term memory, so this research studies the direct relation among these variables and though working memory ideal models are broadly utilized in neuro-scientific and mental research, definitive information about potential variables, for example, sexual orientation is as yet absent. This study was conducted on 50 individuals (25 males and 25 females) among the age of 18 - 25 years. The tool utilised in this study is Corsi Block Test, which is a test that surveys visuo-spatial working memory. The result obtained shows that there is no significant difference in the visuo-spatial working memory of males and females.